Pengaruh Kompetensi dan Kompensasi terhadap Karyawan PT. Pertamina Patraniaga Cikampek - Kanisa Sri Dewi; Novian Ekawaty (STIE AMKOP, 2022)
This study was conducted to analyze the effect of competence and compensation on the performance of employees of PT Pertamina Patraniaga Cikampek. This study used quantitative research methods using descriptive and verification methods. The sample used in this study was 165 people as employees of the distribution section of PT Pertamina Patraniaga Cikampek. using the slovin method and using a random sampling technique from a population of 280 people. The analytical technique used in this research is the technique of scale-range analysis, path analysis using the Method of Succesive Interval (MSI), the Microsoft Excel 2013 computer program and the SPSS version 25 application. There is a positive and significant partial effect of compensation variable on employee performance. And there is a positive and significant influence simultaneously between the variables of competence and compensation on employee performance. Keywords: Competence, Compensation, Employee Performance